2021
DOI: 10.4103/jcn.jcn_198_20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Expressed Breast Milk Alone or in Combination with Paracetamol in Reducing Pain during ROP Screening

Abstract: Introduction: Retinopathy of prematurity (ROP) has been widely acknowledged to be the primary cause of preventable childhood blindness in developing countries. However, the procedure for screening is extremely painful. In this study, we attempted to relieve the pain experienced by these babies using breast milk alone or in combination with oral paracetamol. Materials and Methods: A total of 120 preterm neonates were randomized into three groups: (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Naik A, et al reported that the control and study groups had equal PIPP scores during the ROP. 14,19 There were some limitations in this study. Last feeding time was not documented, which could have impact on pain scores.…”
Section: Discussionmentioning
confidence: 95%
“…Naik A, et al reported that the control and study groups had equal PIPP scores during the ROP. 14,19 There were some limitations in this study. Last feeding time was not documented, which could have impact on pain scores.…”
Section: Discussionmentioning
confidence: 95%